Real-time PCR quantitation of glucocorticoid receptor alpha isoform - Melo, Murilo R (BioMed Central, 2004)
BACKGROUND: The expression of glucocorticoid-receptor (GR) seems to be a key mechanism in the regulation of glucocorticoid (GC) sensitivity and is potentially involved in cases of GC resistance or hypersensitivity. The aim of this study is to describe a method for quantitation of GR alpha isoform (GRα) expression using real-time PCR (qrt-PCR) with analytical capabilities to monitor patients, offering standard-curve reproducibility as well as intra- and inter-assay precision. RESULTS: Standard-curves were constructed by employing standardized Jurkat cell culture procedures, both for GRα and BCR (breakpoint cluster region), as a normalizing gene. We evaluated standard-curves using five different sets of cell culture passages, RNA extraction, reverse transcription, and qrt-PCR quantification. Intra-assay precision was evaluated using 12 replicates of each gene, for 2 patients, in a single experiment. Inter-assay precision was evaluated on 8 experiments, using duplicate tests of each gene for two patients. Standard-curves were reproducible, with CV (coefficient of variation) of less than 11%, and Pearson correlation coefficients above 0,990 for most comparisons. Intra-assay and inter-assay were 2% and 7%, respectively. CONCLUSION: This is the first method for quantitation of GRα expression with technical characteristics that permit patient monitoring, in a fast, simple and robust way.